Enhancing elementary students’ learning outcomes in integrated science and social studies through problem-based learning supported by mind mapping: A classroom action research study - Rahmawati, Nadia Putri; Nuriman, Nuriman; Wardoyo, Arik Aguk; Bayu Setiawan, Ahmad (EduStream: Jurnal Pendidikan Dasar, 2025)
This study employed a classroom action research design to improve students’ learning outcomes in science and social studies through the integration of the Problem-Based Learning (PBL) model supported by a mind-mapping strategy. The research consisted of two cycles, each comprising four stages: planning, action, observation, and reflection. Data were collected through learning outcome tests and observation of student activities. The development of test instruments involved expert validation, empirical validity testing, reliability analysis, difficulty index analysis, and discrimination index analysis. The findings revealed that students’ cognitive achievement in the pre-cycle was still below the expected mastery criteria, with an average score of 68.88. After the implementation of PBL assisted by mind mapping in Cycle I, the average score increased to 76.94, followed by further improvement in Cycle II, reaching an average score of 81.38. Observation results also demonstrated progressive enhancement in classroom learning behaviour, including enthusiasm, activeness in questioning, collaboration, confidence during presentations, ability to construct mind maps, and time management. Overall, the results indicate that the integration of PBL and mind-mapping strategies effectively enhances student learning outcomes by strengthening problem-solving engagement and supporting structured cognitive processing throughout the learning activities.